Selection of reference genes for diurnal and developmental time-course real-time PCR expression analyses in lettuce. Issue 1 (December 2016) - Sgamma, Tiziana; Pape, Judith; Massiah, Andrea; Jackson, Stephen
Abstract Background Real-time quantitative polymerase chain reaction (RT-qPCR) analysis is a low cost and sensitive technique that is widely used to measure levels of gene expression. Selecting and validating appropriate reference genes for normalising target gene expression should be the first step in any expression study to avoid inaccurate results. Results In this study, ten candidate genes were tested for their suitability for use as reference genes in diurnal and developmental timecourse experiments in lettuce. The candidate reference genes were then used to normalise the expression pattern of theFLOWERING LOCUS T (FT ) gene, one of key genes involved in the flowering time pathway whose expression is known to vary throughout the day and at different stages of development. Three reference genes, LsPP2A -1 (PROTEIN PHOSPHATASE 2A -1 ), LsPP2AA3 (PROTEIN PHOSPHATASE 2A REGULATORY SUBUNIT A3 ) andLsTIP41 (TAP42 -INTERACTING PROTEIN OF 41 kDa ), were the most stably expressed candidate reference genes throughout both the diurnal and developmental timecourse experiments. In the developmental experiment using justLsPP2A -1 andLsTIP41 as reference genes would be sufficient for accurate normalisation, whilst in the diurnal experiment all three reference genes, LsPP2A -1, LsPP2AA3 andLsTIP41, would be necessary. TheFT expression pattern obtained demonstrates that the use of multiple and robust reference genes for RT-qPCR expression analyses results in a more accurate and reliable expression profile. Conclusions Reference genes suitable for use in diurnal and developmental timecourse experiments in lettuce were identified and used to produce a more accurate and reliable analysis oflsFT expression levels than previously obtained in such timecourse experiments.